Predicting Motion Patterns Using Optimal Paths - Fromreide, Mads; Hansen, Alex (Frontiers in Physics, 2021)
The ability to navigate safely and efficiently through a given landscape is relevant for any intelligent moving object. Examples range from robotic science and traffic analysis, to the behavior within an ecosystem. Many objects tend to move in patterns depending on their nature. By establishing models of patterns of motion one may estimate the future motion within an area. We propose here a method for detecting regular patterns of motion by modeling the environment as an energy landscape, and locating optimal paths through it. A working algorithm is implemented and applied to maritime traffic systems. The results that are found, show that the method has potential for analyzing and determining regular patterns of motion.